2011
DOI: 10.1007/s00402-011-1418-y
|View full text |Cite
|
Sign up to set email alerts
|

Fall incidence and risk factors in patients after total knee arthroplasty

Abstract: Elderly people who underwent TKA are considered more likely to fall compared with healthy elderly people. For patients with limited knee flexion and ankle plantar flexion, improvement of ROM by exercise therapy and patient education regarding the prevention of falls and fractures are considered necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 38 publications
3
84
0
4
Order By: Relevance
“…Previous studies conducted with TKA patients have presented similar findings although not so positive, starting from Swinkels et al ., (2009) [26], reporting a postoperative fall rate of 24.2%, Matsumoto et al ., (2012) [27], reported fall rate of 32.9% and Levinger et al ., (2012) [28], reported a fall rate at 40%. When comparing postoperative results to preoperative status, a significant difference was reported in fall rate, although Swinkels et al ., (2009) [26], found almost the same results preoperatively and postoperatively and no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted with TKA patients have presented similar findings although not so positive, starting from Swinkels et al ., (2009) [26], reporting a postoperative fall rate of 24.2%, Matsumoto et al ., (2012) [27], reported fall rate of 32.9% and Levinger et al ., (2012) [28], reported a fall rate at 40%. When comparing postoperative results to preoperative status, a significant difference was reported in fall rate, although Swinkels et al ., (2009) [26], found almost the same results preoperatively and postoperatively and no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing postoperative results to preoperative status, a significant difference was reported in fall rate, although Swinkels et al ., (2009) [26], found almost the same results preoperatively and postoperatively and no significant difference. Additionally, Matsumoto et al , (2012) [27], didn’t have a preoperative measurement to compare and Levinger et al ., (2012) [28], reported a reduction in fall rate from 48.5% to 40%, but that difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on falls after THA identifies several risk factors for falls, including polypharmacy, which may be applicable to our patient population because the majority of the SLE group were taking immunosuppressant medications compared with < 1% of the patients with OA 13 . Finally, functional status and strength are also well-known protective factors against falls, including in postoperative total joint arthroplasty patients and in those with rheumatic disease 15,16 . Finally, functional status and strength are also well-known protective factors against falls, including in postoperative total joint arthroplasty patients and in those with rheumatic disease 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been unclear whether patients who have undergone THA or TKA are at higher risk of falling. Matsumoto et al [11] reported that in their age-and gender-matched cohort of 81 patients, who underwent TKA, the incidence of falls was 38% in the first year post-operatively, compared to 24% in non-TKA cohort. These results were lower than previous cohorts of 43% [12], but similar to Ikuotomo et al's [13] THA cohort of 36%, and higher than that reported by Swinkels and Allain [14] and Swinkels et al [15] at 23% and 24% respectively.…”
Section: Introductionmentioning
confidence: 99%